Web-Based General Affair Information System Using Prototyping Method - Amrulloh, Arif; Saintika, Yudha (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2022)
Abstract. Operations are one of the main activities in the company; almost all companies have a General Affairs (GA) section that takes care of all household and operational matters. The bigger the company, the more complex the problems faced. To overcome these problems, the role of technology is needed. In today's digital era, many technologies can be used to assist companies in administrative activities, one of which is a website-based application. Website-based applications have advantages over desktop applications because users only need a browser to access the application. This research will build a web-based general affairs administration system using the prototype method. The prototype is a method that requires the developer's interaction with the client so that it can overcome the incompatibility between the system developer and the client. Tests are carried out using black-box testing techniques focusing on checking system functionality. The results of tests conducted by 26 respondents show that the system built is 100% feasible and meets expectations.